Safety and efficacy of non-steroidal anti-inflammatory drugs to reduce ileus after colorectal surgery - EuroSurg Collaborative (Wiley, 2019)
BACKGROUND: Ileus is common after elective colorectal surgery, and is associated with increased adverse events and prolonged hospital stay. The aim was to assess the role of non-steroidal anti-inflammatory drugs (NSAIDs) for reducing ileus after surgery.